PENERAPAN MODEL BLENDED LEARNING DALAM MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MATERI MENULIS TEKS EKSPLANASI KELAS VIII SMP JAYA KENCANA - Ahmad Jamaludin; Wikanengsih; Yusep Ahmadi F (IKIP Siliwangi, 2022)
This research is motivated by learning that is still conventional and less innovative. Educators must be able to choose interesting learning models so that the learning process is fun and well conveyed. The blended learning model is a solution for delivering material by combining face-to-face learning with online learning. The purpose of this study is to determine the effect of the blended learning model on student learning outcomes in Indonesian subjects with explanatory text material. This study uses a qualitative descriptive method that describes data and facts in the form of descriptions generated from observations and tests. The subject of this study were students of class VIII Â SMP Jaya Kencana Cianjur. The results showed that students could achieve the minimum passing criteria (KKM) 75 % as many as 15 people from 20 students with an average value of 79,75 after the learning action which previously only reached 5% or as 1 person out of 20 students with an average value of 51,25 before the learning action was carried out. It can be concluded that learning using a blended learning model can improve student learning outcomes.